Knowledge, attitude and practices on self-care and nursing needs among older persons of Makassarese Tribe, South Sulawesi, Indonesia - Irwan, Andi Masyitha
Self-care is the action that individuals initiate and perform in order to maintain their own life, health and well-being. Since limited data are available on how Makassarese older persons perform self-care, this study on knowledge, attitude and practices of self-care will help the nurse identify the nursing needs of older persons to help them perform self-care. -- This study aimed to describe the socio demographic profile of Makassarese older persons and to determine their Knowledge, Attitude and Practice on self-care. The research also seek to determine if the relationship between socio demographic and common symptoms experience with KAP is statistically significant and last but not least, to find out the nursing needs of older persons. -- A non experimental descriptive correlational research design was used in the study. A total of 98 respondents participated in the survey with one FGD session consisting of seven participants conducted during the duration of the study. Descriptive statistics were used to analyze the date. In addition, test of association such as Chi square and Fisher exact test were utilized to determine the relationship between KAP and selected variables namely age, gender, marital status, education, occupation, living arrangement and number of common symptom experience. -- Results of the study showed that Makassarese older persons belong to young old with more females compared to males, mostly married, not working, and live with their children. The most common health symptoms were joints pain and around one forth of the respondents suffered from five health symptoms in the last six months. Half of the respondents never go to the hospital and two third of the respondents seek medical/nursing consultation less than three times last year. One third of the respondents went to private clinic to get first aid for their health complaints. As to KAP on self-care Makassarese older persons have fair level of knowledge, positive attitude but had low of practice on self-care, respectively. Results also showed that there is a significant relationship knowledge on self-care and education, attitude on self-care and common symptoms experience, practice on self-care and age gender education. Last but not least, health assessment and medication were identified as the primary nursing needs of this age group. -- It is recommended that improvement access to health care facility of older persons and further research to determine the cause why Makassarese older persons have poor access to health facility need be conducted.